The trinitarian theology of Hilary of Poitiers - Weedman, Mark (Supplements to Vigiliae Christianae ;, 2007)
When Hilary of Poitiers was exiled from his native Poitiers in Gaul to Cappadocia, his entire theological sensibility changed. The Latin bishop, schooled in the tradition of Tertullian and Novatian, became a full-throated participant in the Trinitarian controversies of his time. This book offers a new reading of Hilary's Trinitarian theology that takes into account the historical context of Hilary's thought. It first examines this context and the course of Hilary's engagement with his Homoian opponents. It then turns to the key themes of Hilary's theology as he worked them out in that context.